Creating a culture for information systems success - Belkhamza, Zakariya, 1976-, (Information systems collection., 2015)
It has been widely reported that issues related to organizational context appear frequently in discussions of information systems success. The claim that the information system did not fit the behavioral context in an organization is often part of the explanation of why a particular information system encountered unanticipated resistance and never met expectations. While this context has been intensively studied, we still lack evidence on how this organizational context is affecting the success of information systems from a managerial action perspective. This type of managerial involvement is often neglected to the extent that it becomes a major obstacle to organizational performance. The objective of this book is to assist chief information officers and information technology managers on how to use their managerial actions to create a suitable cultural environment in the organization that leads to a successful implementation of information systems. The book will also provide guidelines for managers on how to create this organizational context, measure it, and make sure it leads to a successful implementation and use of information systems. The book's main theme is to explain how the behavioral context of an organization led by its managers and executives would lead to the success of the information systems function.